Is interculturality possible in multicultural contexts or is just a fashion concept? How do you live it form higher education? - Rossmann Hooker, Tania Patricia (Revista Universitaria del Caribe, 2019)
The issue of Interculturality has meant a challenge for higher education in Latin America, especially in pluricultural contexts. This essay aims to make an approach to some essential elements that cause conflicts between peoples when implementing intercultural policies which are essential for fulfilling this work. A review of existing documents was carried out, as well as experiences. The results are limited to evidence that the construction of relationships to trust and respect are complicated for real, mainly when personal interests prevail and how it ends up impeding the development of peoples and living in harmony, considering the hierarchies that exist between the different peoples and of which the spaces of dialogue and mutual respect are vital, to find a middle ground that benefits everyone and the key question was: Is the concept of interculturality a term of fashion or it simply cannot be understood?